Chitosan Nanocapsules for pH‐Triggered Dual Release Based on Corrosion Inhibitors as Model Study. (7th June 2018) - Pitakchatwong, Chutamart; Schlegel, Isabel; Landfester, Katharina; Crespy, Daniel; Chirachanchai, Suwabun
Abstract: Chitosan (CS) is known for its uniqueness in terms of containing reactive functional groups, i.e., amino and hydroxyl groups, along the chain which offer the noncovalent bonds and chemical modifications. At pH 3 in emulsion system, the CS chains are under charge‐charge repulsive force, leading the polysaccharide chains to align as the hollow nanospheres and at that time, the crosslink leads to the nanocapsules. The CS nanocapsules allow the model cargos, i.e., corrosion inhibitors, entrapment not only via the noncovalent bond based on the weak interaction in the core for 2‐mercaptobenzothiazole (MBT) cargo but also via the chemical bonds based on the amino group remaining on CS structure to result in either amide or Schiff base linkage in case of 3‐nitrosalicylic acid (3NiSA) cargo. The release studies indicate that CS nanocapsules can release two cargoes upon pH change due to the acidic/basic‐triggered cleavage of bonds between cargoes and nanocapsules. Once corrosion occurs, resulting in variation of the local pH value, the CS nanocapsules release MBT in fast and 3NiSA in a slow, sustained manner. The efficiency of the approach is demonstrated using the nanocapsules for hindering the corrosion of copper as measured by electrochemical quartz crystal microbalance. Abstract : The presented concept provides a strategy for designing nanocapsules with controllable two release profiles of corrosion inhibitors. The first inhibitor is released by pH‐sensitive cleavage of chemical bond, while the second inhibitor is released by diffusion through the shell of the nanocapsule. The result shows that nanocapsules with two corrosion inhibitors display a better corrosion protection under neutral condition.